Corporate Support in the Aftermath of a Natural Disaster: Effects on Employee Strains - Sánchez, Juan I.; Korbin, William P.; Viscarra, Diana M. (Academy of Management Journal, 1995)
Relief services provided by corporations to employees following a natural disaster were expected to be associated with reduced levels of employee strains. Data from 143 hurricane victims partially supported this prediction, revealing that tangible support meeting employees' primary needs had the most numerous effects over the course of the disaster aftermath.